2013
DOI: 10.1039/c2dt32094k
|View full text |Cite
|
Sign up to set email alerts
|

Ethanoldecomposition on a Pd(110) surface: a density functional theory investigation

Abstract: Ethanol decomposition on Pd(110) is comprehensively investigated using self-consistent periodic density functional theory. Geometries and energies for all the intermediates involved are analyzed, and the decomposition network is mapped out to illustrate the reaction mechanism. On Pd(110), the most stable adsorption of the involved species tends to follow the gas-phase bond order rules, wherein C is tetravalent and O is divalent with the missing H atoms replaced by metal atoms. The most likely decomposition pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…78 The reaction selectivity toward acetic acid is better understood from the aforementioned reaction energy profiles, keeping in mind the C−H and O−H bond breaking in ethanol catalyzed by Pd have a barrier of <0.8 eV. 79 These steps can be even further activated by the presence of surface hydroxyls, as shown in previous DFT studies.…”
Section: Acs Catalysismentioning
confidence: 95%
“…78 The reaction selectivity toward acetic acid is better understood from the aforementioned reaction energy profiles, keeping in mind the C−H and O−H bond breaking in ethanol catalyzed by Pd have a barrier of <0.8 eV. 79 These steps can be even further activated by the presence of surface hydroxyls, as shown in previous DFT studies.…”
Section: Acs Catalysismentioning
confidence: 95%
“…This is in total agreement with DFT and experimental observations. 20,2325 The temperature-dependent studies showed that ethanol is adsorbed as ethoxy on unsupported polycrystalline Cu, preserving Cα–H and Cβ–H except O–H. 6…”
Section: Outcomes and Discussionmentioning
confidence: 99%
“…We initiate this section by considering routes highlighted in experimental and DFT findings about ethanol activation on TM surfaces. 20,[23][24][25] All likely bond scission paths include Ca-H, Cb-H and O-H in ethanol. We found after the computation of the activation energy for each pathway that there is a remarkable distinction among the different metals.…”
Section: Ethanol Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…While on Pd(111) surface, the most likely decomposition path on Pd(111) surface is CH 3 CH 2 OH * →CH 3 CH 2 O * →CH 3 CHO * →CH 3 CO * →CH 3 * + CO * , in which the initial dehydrogenation is the rate-limited step. (Alcala, Mavrikakis, and Dumesic 2003;Li et al 2010;Guo et al 2013). However, there are still no DFT calculations on the ethanol reforming reaction on a nickel-based catalyst surface.…”
Section: Introductionmentioning
confidence: 96%